MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS (TGT) DALAM PENGUASAAN KOSA KATA BAHASA ARAB - Intan Muflihah; Anggi Rahmadani (KOLONI, 2022)
This research is backgrounded by students' problems in mastering and learning Arabic vocabulary. The factor that affects their abilities is that not all students have studied Arabic before they entered a faith-based school, and teachers still use a less interesting learning model on Arabic vocabulary material, which results in students being less interested and feeling bored during the lesson, so that students' ability to master Arabic vocabulary is low.  To respond to this problem, researchers are interested in using the Teams Games Tournaments (TGT) learning model in improving the mastery of Arabic vocabulary in class X IPA MA Nahdathul Ulama Sumber Agung. The results of this study showed that before the application of the Teams Games Tournaments learning model in mastering Arabic vocabulary of class X IPA MA NU Sumber Agung, from data on the pre-cycle of completed students totaling 6 people (27.2%) while those who were not completed were 16 people (72.7%). Then after the Teams Games Tournaments learning model was applied in mastering Arabic vocabulary, in the first cycle there was an increase from 22 students who completed 11 people (50.0%) and those who did not complete 11 people (50.0%), then in cycle II experienced an increase from 22 students who completed 18 people (81.8%), who had not completed 4 people (18.1%). Thus, it can be seen that the results of the vocabulary mastery test for class X IPA have increased by 54.6%. Based on the results of research and data analysis, it can be concluded that the application of the Teams Games Tournaments learning model can improve the mastery of Arabic vocabulary for class X IPA MA NU Sumber Agung School year 2021/2022. Keywords: Teams Games Tournaments (TGT) Learning Model, Mastery, Arabic Vocabulary.